2019
DOI: 10.1089/wound.2018.0871
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovenous Anastomosis Aids Wound Healing in Lymphedema: Relationship Between Lymphedema and Delayed Wound Healing from a View of Immune Mechanisms

Abstract: Delayed wound healing in lymphedema is assumed to be caused by two reasons, pathophysiological and immunological effects of lymphedema. The aim of this review is to establish how impaired lymphatics alter wound healing pathophysiologically and immunologically, and to propose treatment modalities that can promote wound healing in lymphedema. Lymphaticovenular anastomoses (lymphovenous anastomoses [LVAs]) were performed on patients who had recurrent cellulitis several times with lymphorrhea and developed severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…4 It is conceivable that the lymphedema associated with ENV results in accumulation of excessive protein-rich fluids in the dermis and the subcutaneous tissues, that the protein-rich fluids reduce the immunity of the skin, and that the poor immunity may lead to the disruption of the skin barrier by cutaneous fissures, erosions, and ulcerations. 5 Yoshida et al 6 found that LVA neutralized chronic inflammation by allowing immune cells to return to the circulation; therefore, LVA facilitated wound healing in patients with lymphedema. In our case, LVA contributed to not only reducing the edema but also improving the skin pathology in the right lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…4 It is conceivable that the lymphedema associated with ENV results in accumulation of excessive protein-rich fluids in the dermis and the subcutaneous tissues, that the protein-rich fluids reduce the immunity of the skin, and that the poor immunity may lead to the disruption of the skin barrier by cutaneous fissures, erosions, and ulcerations. 5 Yoshida et al 6 found that LVA neutralized chronic inflammation by allowing immune cells to return to the circulation; therefore, LVA facilitated wound healing in patients with lymphedema. In our case, LVA contributed to not only reducing the edema but also improving the skin pathology in the right lower limb.…”
Section: Discussionmentioning
confidence: 99%
“…The lymphatic vessels transport not only interstitial fluid but also antigen information with dendritic cells to the lymph nodes. From the standpoint of acquired immunity, LVA is thought to create a bypass to the lymph nodes via which dendritic cells can transmit antigen information to T cells in the blood circulation …”
Section: Discussionmentioning
confidence: 99%
“…It is important to monitor patients for lymphedema after surgically invasive procedures to the medial knee region. Lymphedema not only causes edema but also increases the risks of infection and delayed wound healing in the affected limb, which is thought to be caused by localized immune deficiency in the area with lymphedema …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphedema, or the build-up of lymphatic fluid in the interstitial space, is a component of pressure ulcer pathophysiology, but is often studied as a unique entity that can induce ulcer formation. Acquired lymphedema results in increased levels of pro-inflammatory molecules such as TNFα, IL-6, IL-8, and monocyte chemoattractant protein-1 (MCP-1), which contribute to an increase in the infiltration of pro-inflammatory cells, as well as a decrease in T-regulatory cells involved in the resolution of inflammation [36,37]. The impairment of lymphatic clearance, along with impaired venous drainage described above, leads to the maintenance of high leukocyte infiltrate with poor ROS and cytokine clearance.…”
Section: Impaired Lymphatic Drainagementioning
confidence: 99%